2013
DOI: 10.1080/10538712.2013.743950
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents' Lifetime Experience of Selling Sex: Development Over Five Years

Abstract: Lifetime experience of selling sex among adolescents was investigated together with sociodemographic correlates, parent-child relationship, and the existence of people to confide in. Changes over time regarding the selling of sex were investigated through a comparison of data from 2004 and 2009. This study was carried out using 3,498 adolescents from a representative sample of Swedish high school students with a mean age 18.3 years. Of these adolescents, 1.5% stated that they had given sexual services for reim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
78
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(88 citation statements)
references
References 8 publications
6
78
1
3
Order By: Relevance
“…This prevalence is in line with population-based studies from other Western countries (McNeal & Walker, 2016;Mossige, Ainsaar, & Svedin, 2007;Pedersen & Hegna, 2003). Contrary to common beliefs, population-based studies indicate that more boys than girls sell sex for compensation (Fredlund et al, 2013;McNeal & Walker, 2016;Mossige et al, 2007;Pedersen & Hegna, 2003;Svedin & Priebe, 2007). These findings lead to the following questions: Why do adolescents sell sex in social welfare countries such as Sweden?…”
Section: Male Prostitution 11supporting
confidence: 81%
See 2 more Smart Citations
“…This prevalence is in line with population-based studies from other Western countries (McNeal & Walker, 2016;Mossige, Ainsaar, & Svedin, 2007;Pedersen & Hegna, 2003). Contrary to common beliefs, population-based studies indicate that more boys than girls sell sex for compensation (Fredlund et al, 2013;McNeal & Walker, 2016;Mossige et al, 2007;Pedersen & Hegna, 2003;Svedin & Priebe, 2007). These findings lead to the following questions: Why do adolescents sell sex in social welfare countries such as Sweden?…”
Section: Male Prostitution 11supporting
confidence: 81%
“…In relation to the congress, the Swedish Government announced an action plan in 1998 regarding commercial sexual exploitation of children, stating that child sexual exploitation rarely occurred in Sweden (Davidson & Runegrund, 1999;Socialdepartimentet, 1998). However, since this statement studies have found that child sexual exploitation does exist in Sweden and the prevalence of adolescents with the experience of selling sex has been estimated at 1-2% of high school populations (Ahlgren, Näslund, & Roslander, 2009;Fredlund, Svensson, Svedin, Priebe, & Wadsby, 2013;Svedin & Priebe, 2007). This prevalence is in line with population-based studies from other Western countries (McNeal & Walker, 2016;Mossige, Ainsaar, & Svedin, 2007;Pedersen & Hegna, 2003).…”
Section: Male Prostitution 11supporting
confidence: 64%
See 1 more Smart Citation
“…For example, Svedin and Priebe (2007) found that the mental health of Swedish young people (m= 18.2 years) who sold sex was worse, especially among girls, than that of the reference group. Furthermore, studies show that young people involved in selling sex have more problematic relationships with their parents (Edwards, Iritani, & Hallfors, 2006;Fredlund et al, 2013;Johnson, Rew, & Sternglanz, 2006;Kidd & Kral, 2002;Roe-Sepowitz, 2012), less often live with both parents ) and more often live in abusive families (Bagley & Young, 1987;Wilson & Widom, 2010).…”
Section: Socio-demographic and Psychosocial Healthmentioning
confidence: 99%
“…There has been an increase in selling sex among adolescents maybe because it has become easier since the marketplace for selling sex has shifted the arena from being the street to the online world (Cunnigham & Kendall, 2011;Priebe & Svedin, 2012). A recent Swedish study found that 1.5% in a normal sample of 18-year olds had at some time sold sexual services (Svensson et al, 2013) and the reported prevalence from other western countries is of this magnitude (Helweg-Larsen, 2003;Lavoie et al, 2010;Pedersen & Hegna, 2003). Sexual risk behaviours have been shown to be associated with other risk behaviours such as externalizing behaviour problems, antisocial behaviours and substance use (Tubman, 1996) and selling sex among youth has been associated with alcohol and drug use and also antisocial behaviour (Svedin & Priebe, 2004).…”
Section: Sexual Risk Behavioursmentioning
confidence: 98%